Climate changes reconstructed from a glacial lake in High Central Asia over the past two millennia. (10th September 2018) - Lan, Jianghu; Xu, Hai; Sheng, Enguo; Yu, Keke; Wu, Huixian; Zhou, Kangen; Yan, Dongna; Ye, Yuanda; Wang, Tianli
Abstract: Climatic changes in Arid Central Asia (ACA) over the past two millennia have been widely concerned. However, less attention has been paid to those in the High Central Asia (HCA), where the Asian water tower nurtures the numerous oases by glacier and/or snow melt. Here, we present a new reconstruction of the temperature and precipitation change over the past two millennia based on grain size of a well-dated glacial lake sediment core in the central of southern Tianshan Mountains. The results show that the glacial lake catchment has experienced cold-wet climate conditions during the Dark Age Cold Period (∼300–600 AD; DACP) and the Little Ice Age (∼1300–1870 AD; LIA), whereas warm-dry conditions during the Medieval Warm Period (∼700–1270 AD; MWP). Integration of our results with those of previously published lake sediment records, stalagmite δ 18 O records, ice core net accumulation rates, tree-ring based temperature reconstructions, and mountain glacier activities suggest that there has a broadly similar hydroclimatic pattern over the HCA areas on centennial time scale during the past two millennia. Comparison between hydroclimatic pattern of the HCA and that of the ACA areas suggests a prevailing 'warm-dry and cold-wet' hydroclimatic pattern over the whole westerlies-dominated central Asia areas during the past two millennia. We argue that the position and intensity of the westerlies, which are closely related to the phase of the North Atlantic Oscillation (NAO), and the strength of the Siberian High pressure (SH), could have jointly modulated the late Holocene central Asia hydroclimatic changes.